Air Deployed Oceanographic Mooring (ADOM). - EG AND G WASHINGTON ANALYTICAL SERVICES CENTER INC ROCKVILLE MD (1981)
A wide variety of scientific investigations can be pursued with air deployed oceanographic moorings which are configured to specific scientific requirements. Also, a number of important oceanographic studies could be accomplished by deploying oceanographic moorings through the polar sea ice from long-range aircraft. Two systems are being developed: an open ocean moored system, and an ice-covered ocean-suspended system. Both systems are configured to measure temperature, conductivity, and pressure; however, the system design maintains flexibility to allow the addition of other types of sensors. (Author)